Management of Post Harvest losses in maize - Soujanya, P. Lakshmi; Sekhar, J. C.; Kumar, Sangit; Kumar, P.; Hooda, K. S.; Sekhar, Meena (Indian Farming, 2015)
Heavy damage and post harvest losses are experienced by farmers during storage of maize. A large number of biotic factors are responsible for these losses such as, insects, fungi, rodents and birds. The insects alone account for 2 to 4.2 per cent of major food grain loss. Maize infestations start in fields and follow a typical pattern in rural storage where the build-up tends to be slow in the first month after harvest and expands exponentially thereafter.